Barite powder with controllable and regular surface content and preparation method thereof

The preparation of barite powder through thermal cracking technology solved the problems of uneven particle size, irregular particle size and small proportion of stable surfaces in traditional mechanical force preparation, and achieved the comprehensive performance of uniform particle size, regular morphology and large proportion of stable surfaces.

CN119706906APending Publication Date: 2025-03-28GUIZHOU MINZU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411866481.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When traditional mechanical forces prepare barite powder, the particle size is uneven, the particle size is irregular and the stable surface accounts for a small proportion, making it difficult to obtain high-performance powder.

Method used

Barite powder is prepared by thermal cracking technology, and the barite powder is heated by a high-temperature furnace, the temperature is controlled between 400℃ and 600℃, and the temperature conditions are adjusted to control the morphology and particle size distribution of the powder.

Benefits of technology

The preparation of uniform particle size, sheet-like particles and large proportion stabilization surfaces of barite powder is achieved, and the chemical stability, mechanical properties and impurity removal effect of the powder are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706906A_ABST
    Figure CN119706906A_ABST
Patent Text Reader

Abstract

The invention discloses barite powder with controllable and regular surface content and a preparation method of the barite powder. The barite powder is obtained by thermal cracking of barite ore. The specific preparation method comprises the following steps: (1) taking natural high-purity barite ore as a raw material, drying and grinding to obtain barite powder; and (2) the barite powder is placed in a high-temperature furnace to be heated, and barite powder is obtained after heating is completed. By regulating and controlling different thermal cracking temperatures, the barite powder with different surface relative content and cleavage surface proportions can be obtained, thermal cracking fracture of the barite powder shows certain regularity, the number of regular particles exceeds 95%, and the barite powder is excellent in functional characteristic, can be applied to multiple fields such as adsorption and filler, and is wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic powder preparation, and in particular to barite powder with controllable and regular surface content and a preparation method thereof. Background Art

[0002] Barite is a non-metallic mineral product with barium sulfate (BaSO4) as the main component, which is used in many fields. Specifically, barite powder has excellent X-ray and gamma-ray absorption properties and is widely used in radiation shielding materials; barite powder has a high specific gravity and is often used as a weighting material; barite powder has high whiteness, good thermal stability and wear resistance, and is also widely needed in the field of fillers; barite powder also has the characteristics of high density, good filling, non-toxicity and strong inertness, and is widely used in the preparation of many high-end products such as electronic ceramics, magnetic materials, medical industry, coatings, plastics, papermaking, etc.

[0003] The functional properties of barite powder, such as surface effect, optical properties, strength, magnetism, chemical activity and catalytic performance, vary with particle size, morphology and fracture surface. For example, when used as an additive for high-density radiation shielding concrete, barite powder with a particle size of 250 to 600 μm can increase the density, compressive strength and porosity of the blend, thereby enhancing the shielding performance; when preparing low-resistivity composite conductive powders with antimony-doped tin oxide, the irregular shape of the barite powder will affect the performance of the coating, resulting in poor coating uniformity, increased surface roughness and poor adhesion. In addition, when used as an adsorbent for anions and metal ions, due to the large relaxation amplitude of barium ions and sulfate ions on the (001) surface of barite powder, its surface becomes an ideal adsorption site. When the (001) surface of barite powder accounts for a smaller proportion, the adsorption capacity and adsorption stability of the barite powder will deteriorate.

[0004] At present, the methods for processing barite raw materials into barite powder include autogenous grinding, rod milling, ball milling and air flow milling. The stress of the above traditional mechanical processing methods acts disorderly on the various crystal planes of barite, making the crystal structure of the barite raw material disordered, and the traditional cleavage pattern of barite minerals weakened, resulting in difficulty in preserving the cleavage planes, making it difficult to obtain high-performance powder.

[0005] Therefore, there is an urgent need for a method for preparing barite powder with uniform particle size, flaky particles and a large proportion of stable surfaces. Summary of the invention

[0006] The purpose of the present invention is to provide a barite powder with controllable and regular surface content and a preparation method thereof, so as to solve the problems of uneven particle size, irregular particles and a small proportion of stable surface of the barite powder prepared by the above-mentioned traditional mechanical force.

[0007] To achieve the above objectives, the first aspect of the present invention provides a barite powder with controllable and regular surface content, wherein the barite powder is obtained by thermal cracking of barite ore.

[0008] Preferably, the barite powder includes one or both of {001} surfaces and {210} surfaces.

[0009] Preferably, the ratio of the {001} surface to the {210} surface in the barite powder is 1:(1.1-1.5).

[0010] More preferably, the ratio of the {001} surface to the {210} surface in the barite powder is 1:(1.15-1.25).

[0011] Preferably, the barite powder is in the shape of regular flakes.

[0012] Preferably, the contact angle of the barite powder is 83° to 100°.

[0013] A second aspect of the present invention provides a method for preparing barite powder with controllable and regular surface content, comprising the following steps:

[0014] (1) Using natural high-purity barite ore as raw material, drying and grinding to obtain barite powder;

[0015] (2) The barite powder is placed in a high temperature furnace for heating, and after the heating is completed, the barite powder is obtained.

[0016] Preferably, in step (1), the content of barium sulfate in the natural high-purity barite ore is greater than 95%.

[0017] Preferably, in step (1), the particle size of the barite powder is 0.5 cm to 1 cm.

[0018] Preferably, in step (2), the heating temperature is 400°C to 600°C.

[0019] Preferably, in step (2), the heating time is greater than 2 hours.

[0020] Therefore, the present invention adopts a barite powder with controllable and regular surface content and a preparation method thereof of the above structure, which has the following beneficial effects:

[0021] (1) Barite ore itself is brittle and its surface exhibits various anisotropies. The present invention provides thermal stress to the barite ore during the thermal cracking process, and the fracture of the barite particles exhibits a certain regularity. The present invention can effectively control the morphology and particle size distribution of the barite powder by adjusting different temperature conditions.

[0022] (2) The present invention makes the particle surface content of barite powder highly controllable by regulating different pyrolysis temperatures. According to the results of X-ray diffraction analysis, the relative content of the barite powder surface is different and the proportion of cleavage plane is different.

[0023] (3) Different minerals have different thermal expansion properties, so they are prone to anisotropic fracture, thereby removing impurities in associated minerals. The present invention can improve the impurity removal effect through thermal cracking.

[0024] (4) According to the observation under scanning electron microscope, the number of regular particles in the barite powder of the present invention exceeds 95%, and only a small amount of fine debris exists. The effective output of the barite powder prepared by the present invention is high.

[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the XRD diagram of natural high-purity barite ore;

[0027] Figure 2 It is the crystal system of natural high-purity barite ore;

[0028] Figure 3 XRD diagram of the barite powder prepared in Examples 1 to 3;

[0029] Figure 4 The XRD diagram of the barite powder prepared in Comparative Examples 1 and 2;

[0030] Figure 5 This is the XRD pattern of the barite powder prepared in Comparative Example 4;

[0031] Figure 6 The SEM images of the barite powders prepared in Examples 1 to 3 are as follows;

[0032] Figure 7 The SEM images of the barite powders prepared in Comparative Examples 1 and 2 are as follows;

[0033] Figure 8 The SEM images of the barite powders prepared in Comparative Example 2 and Example 3 are shown;

[0034] Fig. 9 This is the SEM image of the barite powder prepared in Comparative Example 3;

[0035] Fig.10 This is a SEM image of the barite powder prepared in Comparative Example 4;

[0036] Fig.11 is the contact angle of the barite powder prepared in Comparative Example 1 and Examples 1 to 3;

[0037] Fig.12 The adsorption performance of the barite powder prepared in Comparative Example 1;

[0038] Fig.13 The adsorption performance of the barite powder prepared in Example 3;

[0039] Fig.14 These are infrared spectra of sodium metasilicate nonahydrate, the barite powder prepared in Comparative Example 1 after adsorption, and the barite powder prepared in Example 3 after adsorption. DETAILED DESCRIPTION

[0040] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0041] Example 1

[0042] A method for preparing barite powder with controllable and regular surface content, comprising the following steps:

[0043] (1) Using natural high-purity barite ore as raw material, the content of barium sulfate in the natural high-purity barite ore is greater than 95%, and the specific content of each component is shown in Table 1, and then drying and grinding to obtain barite powder, the particle size of the barite powder is 0.5 cm;

[0044] Table 1 Composition of natural high purity barite ore

[0045]

[0046] It can be seen from Table 1 that the content of barium sulfate in natural high-purity barite ore is 96.7%, exceeding 95%.

[0047] XRD characterization of natural high-purity barite ore, the analysis results are shown in Figure 1 The barite ore used in this embodiment belongs to the orthorhombic system. Figure 2 .

[0048] (2) The barite powder is placed in a high-temperature furnace and heated at a temperature of 400° C. for 2 h. After the heating is completed, barite powder is obtained.

[0049] Example 2

[0050] The difference between this embodiment and embodiment 1 is that the heating cracking temperature is different. The heating temperature in this embodiment is 500°C.

[0051] Example 3

[0052] The difference between this embodiment and embodiment 1 is that the heating cracking temperature is different. The heating temperature in this embodiment is 600°C.

[0053] Comparative Example 1

[0054] The difference between this comparative example and Example 1 is that the treatment method of barite ore is different. This comparative example uses the method of autogenous grinding to crack the barite ore. The specific treatment method in this comparative example is as follows:

[0055] Place the barite ore of about 0.5 mm in size into a ceramic mortar and grind it using a steady, even kneading motion until the required particle size reaches 200 mesh to obtain a powder sample.

[0056] Comparative Example 2

[0057] The difference between this comparative example and Example 1 is that the treatment method of the barite ore is different. This comparative example uses a mechanical method to crack the barite ore. The specific treatment method in this comparative example is as follows:

[0058] Put the barite ore of about 0.4mm into the laboratory ball mill, use the prepared stainless steel balls as the grinding medium, fill the bed voids at a ratio of 50%, grind at a speed of 750r / min, take samples at regular intervals, and grind for 2, 4, 6, and 8h respectively to obtain powder samples.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 1 is that the heating cracking temperature is different, and the heating temperature in this comparative example is 300°C.

[0061] Comparative Example 4

[0062] The difference between this comparative example and Example 1 is that the heating cracking temperature is different, and the heating temperature in this comparative example is 700°C.

[0063] Test example

[0064] (1) XRD characterization was performed on the barite powders prepared in the examples and comparative examples.

[0065] The XRD characterization results of Examples 1 to 3 and Comparative Examples 1 to 2 and Comparative Example 4 are shown in Figure 3 to Figure 5 .from Figure 1 It can be seen that the {001} surface and {210} surface account for a large proportion in the barite powder prepared in Example 1, the {210} surface accounts for a large proportion in the barite powder prepared in Example 2, and the {001} surface and {210} surface account for a large proportion in the barite powder prepared in Example 3. Figure 4 It can be seen that the {001} surface and {210} surface account for a small proportion in the barite powder prepared by autogenous grinding (Comparative Example 1) and mechanical grinding cracking (Comparative Example 2). Figure 5It can be seen that the barite powder obtained by thermal cracking at 700°C in Comparative Example 4 still contains a large amount of {001} surfaces and {210} surfaces.

[0066] according to Figure 1 The relative content of each surface can be obtained from the peak value in the graph, and the proportion of the cleavage surface can be determined from this. In Example 1, the ratio of the {001} surface to the {210} surface is about 1:1.21, in Example 2, the ratio of the {001} surface to the {210} surface is about 1:1.77, and in Example 3, the ratio of the {001} surface to the {210} surface is about 1:1.16. Figure 4 It can be seen that the ratio of the {001} surface to the {210} surface in Comparative Example 1 is approximately 1:1.86.

[0067] Therefore, the cleavage surface of the barite powder prepared by thermal cracking of the present invention accounts for a large proportion. Under autogenous and mechanical grinding cracking, the cleavage surfaces of the barite powder {001} and {210} account for a small proportion. The thermal cracking barite powder of the present invention produces defects along the cleavage surface according to the surface anisotropy of the barite itself, and the unstable surface produces defects during thermal expansion. The cleavage surface is cracked along the cleavage surface. At 400°C, the two cleavage surfaces {001} and {210} are mainly produced, and at 500°C, the {210} cleavage surface is mainly produced, which solves the problems of chemical stability, mechanical properties, and difficulty in controlling particle size changes of the barite powder.

[0068] (2) The barite powders prepared in the examples and comparative examples were characterized by SEM.

[0069] The SEM characterization results of the barite powders prepared in Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Figure 6 to Figure 10 .from Figure 6 It can be seen from the above that the barite powders prepared by thermal cracking at a specific temperature in the examples all present regular flakes. Figure 7 It can be seen that the particle size distribution of the barite powder obtained by autogenous grinding and cracking in Example 1 is extremely uneven, and the morphology of the barite powder obtained by mechanical grinding and cracking in Example 2 is extremely irregular, indicating that the thermal cracking process in the present invention is superior to the traditional autogenous grinding and mechanical grinding cracking process. Figure 8 It can be seen that the disordered force in the mechanical grinding of Comparative Example 2 acts on each surface of the barite, resulting in uneven particle size, irregular particles, and a large amount of debris on the particle surface without cleavage characteristics. The diffraction peaks corresponding to each surface gradually decrease, and the proportion of the {001} and {210} surface contents decreases; while in Example 3, the thermal stress acts on the unstable surface, and after cracking, the particles are mainly flaky particles, which are composed of stable flaky cleavage surfaces, and the particle surface contains a large number of cleavage steps.

[0070] from Fig. 9It can be seen that in Comparative Example 3, the barite is heated to 300°C, and the surface cleavage is observed by scanning electron microscopy. The barite ore has just started to crack at this temperature, and has not yet completely cracked into barite powder. Therefore, this temperature is the first cracking temperature of barite. Below 300°C, the barite is not broken, and after 300°C, it continues to crack to form barite powder.

[0071] from Fig.10 It can be seen that in Comparative Example 4, the barite is heated to 700°C. Although X-ray diffraction at 700°C shows that the powder still contains a large number of {001} and {210} surfaces, and some particles of the barite powder are still flaky, due to excessive cracking, the powder contains a large amount of fine debris, resulting in uneven distribution of powder particle size.

[0072] Therefore, the present invention obtains barite powder with regular particle size and morphology by thermal stress cracking of barite, and the thermal cracking temperature should not be lower than 400°C and higher than 600°C. At a thermal cracking temperature of 300°C, barite cannot be cracked to obtain powder at the beginning, and at a thermal cracking temperature of 700°C, it is over-cracked and the powder is uneven. In the present invention, if a powder containing a large amount of {001} surface is required, the barite can be heated to 400°C, and if a powder containing a large amount of {210} surface is required, the barite can be heated to 500°C. The present invention performs thermal cracking at a fixed temperature to take into account the comprehensive performance of uniform particle size distribution, regular morphology and a large proportion of stable surfaces of the barite powder.

[0073] (3) The contact angles of the barite powders prepared in the examples and comparative examples were tested.

[0074] Test results see Fig.11 ,from Fig.11 It can be seen that the contact angle of the powder prepared by the traditional self-grinding method in Comparative Example 1 is 80°. As the thermal cracking temperature increases, the contact angle first increases and then decreases, with a maximum of 100°. The contact angle of the traditional cracked barite powder is smaller than that of the powder cracked under thermal stress, mainly because the powder contains a large number of {001} surfaces and {210} surfaces with small surface energy, low surface energy, and low wettability, resulting in a large contact angle, indicating that the powder has relatively stable performance and good processing performance.

[0075] (4) The adsorption performance of the barite powder prepared in the embodiment and the comparative example was tested.

[0076] The barite powder prepared in Example 3 and Comparative Example 1 was added to a 0.01 mol / L sodium metasilicate nonahydrate solution, and adsorbed under magnetic stirring for 1.5 hours. After the adsorption was completed, the mixture was filtered and dried to obtain adsorbed barite powder. The adsorbed barite powder was crushed and sieved through 200 mesh to obtain crushed barite powder. The sodium metasilicate nonahydrate, the barite powder prepared in Example 3 and Comparative Example 1, the barite powder after adsorption of sodium metasilicate in Example 3 and Comparative Example 1, and the crushed barite powder were characterized by infrared spectroscopy. Fig.12 It can be seen that the barite powder obtained by conventional processing (Comparative Example 1) has a poor adsorption effect, with only 484.6 cm -1 There is an absorption peak at Fig.13 and Fig.14 It can be seen that the barite powder obtained by cracking under thermal stress in Example 3 has a good adsorption effect. -1 、877.3cm -1 、484.6cm -1 There are absorption peaks at all places, indicating that the powder has good adsorption performance, stable chemical properties and good mechanical properties.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A barite powder with controllable and regular surface content, characterized in that: Barite powder is obtained by thermal cracking of barite ore.

2. A barite powder with controllable and regular surface content according to claim 1, characterized in that: The barite powder includes one or both of {001} surfaces and {210} surfaces.

3. A barite powder with controllable and regular surface content according to claim 1, characterized in that: Barite powder is in regular flake shape.

4. The barite powder with controllable and regular surface content according to claim 1, characterized in that: The contact angle of barite powder is 83°~100°.

5. The method for preparing a barite powder with controllable and regular surface content according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Using natural high-purity barite ore as raw material, drying and grinding to obtain barite powder; (2) The barite powder is placed in a high-temperature furnace and heated. After the heating is completed, the barite powder is obtained.

6. A method for preparing a barite powder with controllable and regular surface content according to claim 5, characterized in that: In step (1), the content of barium sulfate in the natural high-purity barite ore is greater than 95%.

7. The method for preparing a barite powder with controllable and regular surface content according to claim 5, characterized in that: In step (1), the particle size of the barite powder is 0.5 cm to 1 cm.

8. The method for preparing a barite powder with controllable and regular surface content according to claim 5, characterized in that: In step (2), the heating temperature is 400°C to 600°C.

9. The method for preparing a barite powder with controllable and regular surface content according to claim 5, characterized in that: In step (2), the heating time is greater than 2 hours.